Assessing Learners' Understanding of Microbiology Applications in Multidisciplinary Biological Science Degree Madira Coutlyne Manganyia - Manganyi, Madira (Research in Social Sciences and Technology, 2025)
This study investigates the comprehension of microbiological concepts among students and identifies areas for improvement in microbiology education. The participants comprised 56 second-year learners (17 males, 39 females) studying microbiology as part of their BSc Biology program at a university in South Africa’s Eastern Cape. A survey was conducted to assess respondents' accuracy in answering ten questions covering various aspects of microbiology, including definitions, classifications, historical figures, and applications in different disciplines. The results of the survey on microbiology knowledge revealed that respondents performed best in identifying Antonie van Leeuwenhoek, with an accuracy rate of 85.7%. Conversely, they performed worst in accurately identifying the reasons to study microbiology, with only 10.7% of responses being accurate. The results reveal varying levels of accuracy, with notable strengths in historical knowledge and identification of infectious diseases. However, deficiencies are observed in taxonomical classifications and understanding of interdisciplinary applications. Strategies for addressing these gaps through targeted educational interventions, curriculum development, and innovative pedagogical approaches are discussed. Overall, this study underlines the importance of ongoing efforts to enhance microbiology education and prepare students for the complexities of the field.